Stating Values through Denial of Substance: Implementation of One Cognitive Mechanism in the Russian Substandard - Ukhanova, Tatiana V.; Kosova, Vera A.; Antonakova, Darina (Journal of History Culture and Art Research, 2017)
The article is devoted to the study of objectification in the substandard forms of Russian language concerning the conceptual norm of possession, which represents the axiological aspect of the world picture by sociolect holders. The relevance of the work is determined by the belonging of the indicated problem to the field of the interest intersection from the theory of nomination, cognitive linguistics and social linguistics, and at the same time, by an insufficient knowledge of the implementation means in the mechanism language of value marking concerning socially separate groups of Russian mentality bearers. In Russian language, the cognitive mechanism of value assertion through the negation of a substance is realized through the word-formation category "an attribute for the lack of substance", which belongs to the number of productive nominative categories. Our task was a complex structural and functional description of sub-standard derivatives of this category with the aim to their further comprehension from onomasiologic and cognitive positions. This conditioned the use of word-formation and component analysis methods. Basing on the works by E.S. Kubryakova and N.D. Arutunova, we determined the essence of the Russian mental norm of possession. The model of field organization proposed by us concerning the mental norm of possession made it possible to draw the conclusion about the complexity of the value basis organization concerning the Russian national worldview, determining the role in which the spiritual and moral guidelines play an important role, and the material values located on the periphery are less significant. The results of the research can be applied in the field of linguistic didactics, especially in the practice of teaching Russian as a foreign language, as well as in the organization of associative and social linguistic experiments.